Mechanical Properties of Commercial Recycled Polypropylene from Plastic Waste - Handayani, Sri Utami; Fahrudin, Muhamad; Mangestiyono, Wiji; Hadi Muhamad, Alaya Fadlu (Vocational College of Universitas Diponegoro, 2021)
In Indonesia increasing the use of plastic will increase plastic waste because waste management in Indonesia is still poor. Plastics can be recycled and used to make plastic bags, toys and various household utensils, but their use is still very limited. This limitation is because the strength of recycled plastic is not as good as virgin plastic pellets, so the resulting product tends to be brittle. This study aims to determine the mechanical properties of plastics made from recycled polypropylene plastic. Five specimens are made according to the ASTM D 638 type II standard. The results show that yield strength is 16.357±2.65 MPa, elastic modulus 295,926 ± 41,97 MPa and ultimate tensile stress 19,701±1,261 MPa. The yield stress of recycled polypropylene has a lower value than the yield stress on recycled polypropylene studied by Abdelhaleem et.al or Barbosa et.al which is around 21 MPa[7][5]. This difference is possible due to the different quality of raw materials and processing.